Transcendence and immanence into or onto creative pluralism in South Africa - Rooyen, Johan A. van (HTS teologiese studies, 2021)
Two philosophical tools are used in this article, namely (1) that of philosophical-pluralism and (2) transcendent pluralism as a kind of glue to enhance our examining of creative pluralism. There is a diversity implant in positive modus of understanding this pluralistic pristine of creative pluralism within transcendence modus. To help facilitate this pluralistic pristine, the author makes use of three constructivist paradigms that are distinguished and used, namely (1) exogenous constructivism (rooted in a mechanistic metaphor) emphasising the reconstruction of structures preformed in the environment; (2) endogenous constructivism (rooted in an organismic metaphor) emphasising the coordination of previous organismic structures and (3) dialectical constructivism (rooted in a contextualistic metaphor) emphasising the construction of new structures out of organism and environmental interaction.Contribution: The aim of this article is to present a coherent metatheory by specifying the boundary conditions in which each root metaphor (constructive pluralism) best applies. These above-mentioned versions of pluralism as tools are a reminiscence and a jubilee of the efforts made by sapiens through diversity onto or into pluralism to enable the religious hamlet to think and share. This pluralistic approach of orientation, I hope, will empower sapiens in their respective hamlets to define, articulate and designate to enhance their own epistemological and ontological vantage points wherefrom their individual, coherent and contextual ways of thinking, acting and projecting their lives in a positive modus by emphasising the reconstructions of their performance in their environment.